Sosiologi Pendidikan Sebagai Ilmu Pengetahuan - Wardani Sihaloho; Wildani Wildani; Siti Halisah; Anti Pebriani Syahpitri; Khoilula Hanum Tanjung (Jurnal Dirosah Islamiyah, 2023)
In the Indonesian context, the sociology of education is becoming increasingly relevant because Indonesia has a complex and diverse education system, and there are still many challenges that must be faced in improving the quality of education. Educational issues cover various aspects related to education, such as access to education, quality of education, and educational disparities. In this study, literature studies were used to find sources of information to find scientific research based on relevant literature on the topic in question and theory. This type of library research is related to library data collection, obtaining information from various libraries, one of which is scientific journals. The implications of the sociology of education in education are that education must consider social factors such as social class, gender, race, and religion in designing educational programs that are more inclusive and effective. Key words: Social, science, education, interaction